2002
DOI: 10.5014/ajot.56.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Processing Issues Associated With Asperger Syndrome: A Preliminary Investigation

Abstract: This study provides initial evidence that clear differences exist in the sensory processing patterns of children with Asperger syndrome when compared with peers without disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
98
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(108 citation statements)
references
References 22 publications
5
98
0
5
Order By: Relevance
“…By contrast, they also show reduced responsiveness and registration of input (such as failing to orient to novel stimuli or react when their name is being called) as well as sensory seeking behaviours (Kern et al 2007). While the causes of atypical sensory processing in ASD are unclear, the pattern of concurrent increased and reduced responding to sensory stimulation is indicative of a difficulty managing one's response to sensory input, rather than having a specific style of atypical processing (Dunn et al 2002). There appears to be overlap between the patterns of sensory modulation atypicalities that occur within each condition, whereby sometimes individuals exhibit heightened responses to sensory events and at other times fail to attend to them.…”
Section: Alexithymia and Sensory Processing Atypicalitiesmentioning
confidence: 99%
“…By contrast, they also show reduced responsiveness and registration of input (such as failing to orient to novel stimuli or react when their name is being called) as well as sensory seeking behaviours (Kern et al 2007). While the causes of atypical sensory processing in ASD are unclear, the pattern of concurrent increased and reduced responding to sensory stimulation is indicative of a difficulty managing one's response to sensory input, rather than having a specific style of atypical processing (Dunn et al 2002). There appears to be overlap between the patterns of sensory modulation atypicalities that occur within each condition, whereby sometimes individuals exhibit heightened responses to sensory events and at other times fail to attend to them.…”
Section: Alexithymia and Sensory Processing Atypicalitiesmentioning
confidence: 99%
“…VerMaas Lee noted that auditory and proprioreceptive items most strongly differentiated autistic and control groups but that differences were apparent in all sensory domains examined. In another study, Dunn, Myles, and Orr (2002) found a clear difference in the sensory defensiveness patterns of children with Asperger syndrome versus children without disabilities. In summary, these and other studies demonstrate that sensory defensiveness is much more common in children with autism than in typically developing children.…”
Section: Association Of Sensory Defensiveness With Other Childhood Bementioning
confidence: 99%
“…Children with autism and children with fragile X syndrome had markedly elevated scores in sensory reactivity and sensory sensitivities in relation to the other groups. When the full version of the Sensory Profile (Dunn, 1999), a 125-item questionnaire, was administered to parents of older children with autism, the most frequently endorsed items were "hypersensitivity to touch and to auditory input" (Kientz & Dunn, 1997).These difficulties appear to occur across the ASD spectrum, including in children with Asperger syndrome (Dunn, Myles, & Orr, 2002;Dunn, Saiter, & Rinner, 2002;Myles et al, 2004). Using the Dunn (1999) sensory profile across the lifespan, Kern et al (2006) provide evidence that sensory processing abnormalities involve multiple modalities (e.g.…”
mentioning
confidence: 99%
“…These difficulties appear to occur across the ASD spectrum, including in children with Asperger syndrome (Dunn, Myles, & Orr, 2002;Dunn, Saiter, & Rinner, 2002;Myles et al, 2004). Using the Dunn (1999) sensory profile across the lifespan, Kern et al (2006) provide evidence that sensory processing abnormalities involve multiple modalities (e.g.…”
mentioning
confidence: 99%